Pelatihan Membuat Media Promosi Sederhana dengan Aplikasi Canva untuk Guru Sekolah Dasar - Rismayani, Rismayani (INCOME: Indonesian Journal of Community Service and Engagement, 2022)
Currently in the industrial era 4.0, promotional media are often divided into two parts, namely online and offline media. Learning media using interactive canvas applications has a good design, unique and easy for students to remember so that they are moved to do what is conveyed. Therefore, the introduction and training of the Canva application as a learning medium was applied to community service partners for Weragati II State Elementary School teachers in Palasah District, Majalengka Regency. This Community Service activity is carried out using lecture, demonstration and practical methods. As a result of this activity, participants can receive and can use the Canva application.